Nb and Pd co-doped La0.57Sr0.38Co0.19Fe0.665Nb0.095Pd0.05O3-das a stable, high performance electrode for barrier-layer-free Y2O3-ZrO2electrolyte of solid oxide fuel cells - Chen, K.; He, S.; Li, N.; Cheng, Y.; Ai, N.; Chen, M.; Rickard, William; Zhang, T.; Jiang, S. (Elsevier SA, 2018)
© 2017 Elsevier B.V. La 0.6 Sr 0.2 Co 0.2 Fe 0.8 O 3-d (LSCF) is the most intensively investigated high performance cathode for intermediate temperature solid oxide fuel cells (IT-SOFCs), but strontium segregation and migration at the electrode/electrolyte interface is a critical issue limiting the electrocatalytic activity and stability of LSCF based cathodes. Herein, we report a Nb and Pd co-doped LSCF (La 0.57 Sr 0.38 Co 0.19 Fe 0.665 Nb 0.095 Pd 0.05 O 3-d , LSCFNPd) perovskite as stable and active cathode on a barrier-layer-free anode-supported yttria-stabilized zirconia (YSZ) electrolyte cell using direct assembly method without pre-sintering at high temperatures. The cell exhibits a peak power density of 1.3 W cm -2 at 750 °C and excellent stability with no degradation during polarization at 500 mA cm -2 and 750 °C for 175 h. Microscopic and spectroscopic analysis show that the electrochemical polarization promotes the formation of electrode/electrolyte interface in operando and exsolution of Pd/PdO nanoparticles. The Nb doping in the B-site of LSCF significantly reduces the Sr surface segregation, enhancing the stability of the cathode, while the exsoluted Pd/PdO nanoparticles increases the electrocatalytic activity for the oxygen reduction reaction. The present study opens up a new route for the development of cobaltite-based perovskite cathodes with high activity and stability for barrier-layer-free YSZ electrolyte based IT-SOFCs.